Kandungan nutrien kulit pisang kepok (Musa paradisiaca) yang difermentasi dengan cairan rumen kambing - Maria Theresia Sa'o; Tri Anggarini Yuniwaty Foenay; Theresia Nur Indah Koni (Jurnal Ilmu Peternakan Terapan, 2021)
The purpose of this study was to determine the nutritional content of fermented Kepok banana peel flour (Musa paradisiaca) by goat rumen liquid. This study was designed using a completely randomized design (CRD) with 4 treatments and 5 replications. The four treatments were P0: Kepok banana peel flour + 0% goat rumen fluid (control), P1: Kepok banana peel flour + 30% goat rumen fluid, P2: Kepok banana peel flour + 40% goat rumen fluid, P3: Kepok banana peel flour + 50% goat rumen fluid. The fermentation process was carried out for 7 days. The results of this study showed that the use of goat rumen fluid changed (P<0.05) the nutrient content of fermented Kepok banana peel flour. The use of 50% goat rumen fluid increased crude protein and crude fat content, however reduced the dry matter and crude fiber content of Kepok banana peel flour.